Weather omens of Enūma Anu Enlil : thunderstorms, wind and rain (tablets 44-49) - Gehlken, Erlend. (Cuneiform Monographs, 2012)
The Assyro-Babylonian omen series Enūma Anu Enlil , written on seventy cuneiform tablets, bears witness to the early understanding of the mutual interactions of heaven and earth on both the physical and the religious levels. To facilitate accessibility, technical and linguistic commentaries as well as an excerpt series were compiled by the scholars of old. This ancient knowledge, which was still largely characterized by mythological concepts, was never completely abandoned, not even when the 'calculating' astronomy became prevalent in the first millennium B.C. The series deals in four parts with the moon, the sun, weather phenomena, and fixed stars and planets. This book offers an edition of the texts of the second half of the weather section with the accompanying material.